- Учителю
- Логические примеры на уроках математики 1-4 класс.
Логические примеры на уроках математики 1-4 класс.
1 1 1 1 1 = 1 | 3 3 3 = 3 | 1 1 1 1 1 = 3 |
3 3 3 3 = 6 | 2 2 2 2 2 = 10 | 3 3 3 3 = 0 |
2 2 2 2 2 = 6 | 3 3 3 3 3 = 9 | 2 2 2 2 2 = 5 |
Решение:
1 + 1 + 1 - 1 - 1 = 1
3 + 3 - 3 = 3
1 + 1 + 1 + 1 - 1 = 3
3 + 3 + 3 - 3 = 6
2 + 2 + 2 + 2 + 2 = 10
3 + 3 - 3 - 3 = 0
2 + 2 + 2 + 2 - 2 = 6
3 + 3 + 3 + 3 - 3 = 9
2 + 2 + 2 + 2 + 2 = 10
2.
3 3 3 3 = 0
2 2 2 2 2 = 6
3 3 3 3 3 = 9
2 2 2 2 2 = 2
3 3 3 3 3 = 3
1 1 1 1 1 = 8
3 3 3 3 3 3 = 6
2 2 2 = 6
3 3 3 3 3 3 = 0
Решение:
3 + 3 - 3 - 3 = 0
2 + 2 + 2 + 2 - 2 = 6
3 + 3 + 3 + 3 - 3 = 9
2 + 2 + 2 - 2 + 2 = 2
3 + 3 + 3 - 3 + 3 = 3
11 - 1 - 1 - 1 = 8
3 + 3 + 3 + 3 - 3 - 3 = 6
2 + 2 + 2 = 6
3 + 3 + 3 - 3 - 3 - 3 = 0
3.
2 2 2 = 2
3 3 3 3 3 3 3 = 9
2 2 2 2 = 8
3 3 3 3 3 3 3 = 3
2 2 2 2 = 4
3 3 3 3 3 3 3 3 = 6
2 2 2 2 = 0
3 3 3 3 3 3 3 3 = 0
2 2 2 2 2 2 = 8
Решение:
2 + 2 - 2 = 2
3 + 3 + 3 + 3 + 3 - 3 - 3 = 9
2 + 2 + 2 + 2 = 8
3 + 3 + 3 + 3 - 3 - 3 - 3 = 3
2 + 2 + 2 - 2 = 4
3 + 3 + 3 + 3 + 3 - 3 - 3 - 3 = 6
2 + 2 - 2 - 2 = 0
3 + 3 + 3 + 3 - 3 - 3 - 3 - 3 = 0
2 + 2 + 2 + 2 + 2 - 2 = 8
4.
2 2 2 2 2 2 = 4
3 3 3 3 3 3 3 3 = 3
2 2 2 2 2 2 = 0
4 4 4 = 12
2 2 2 2 2 2 2 = 10
4 4 4 = 4
2 2 2 2 2 2 2 = 6
4 4 4 4 = 8
2 2 2 2 2 2 2 = 2
Решение:
2 + 2 + 2 + 2 - 2 - 2 = 4
3 + 3 + 3 + 3 + 3 - 3 - 3 - 3 - 3 = 3
2 + 2 + 2 - 2 - 2 - 2 = 0
4 + 4 + 4 = 12
2 + 2 + 2 + 2 + 2 + 2 - 2 = 10
4 4 4 = 4
2 + 2 + 2 + 2 + 2 - 2 - 2 = 6
4 + 4 + 4 - 4 = 8
2 + 2 + 2 + 2 - 2 - 2 - 2 = 2
5.
4 4 4 4 = 0
2 2 2 2 2 2 2 2 = 8
2 2 2 2 2 2 2 2 = 4
4 4 4 4 4 = 4
4 4 4 4 4 4 = 8
2 2 2 2 2 2 2 2 = 0
4 4 4 4 4 4 = 0
2 2 2 2 2 2 2 2 2 = 10
4 4 4 4 4 4 4 = 4
Решение:
4 + 4 - 4 - 4 = 0
2 + 2 + 2 + 2 + 2 + 2 - 2 - 2 = 8
2 + 2 + 2 + 2 + 2 - 2 - 2 - 2 = 4
4 + 4 + 4 - 4 - 4 = 4
4 + 4 + 4 + 4 - 4 - 4 = 8
2 + 2 + 2 + 2 - 2 - 2 - 2 - 2 = 0
4 + 4 + 4 - 4 - 4 - 4 = 0
2 + 2 + 2 + 2 + 2 + 2 + 2 - 2 - 2 = 10
4 + 4 + 4 + 4 - 4 - 4 - 4 = 4
6.
2 2 2 2 2 2 2 2 = 8
4 4 4 4 4 = 4
2 2 2 2 2 2 2 2 2 = 6
4 4 4 4 4 4 = 0
5 5 5 = 5
2 2 2 2 2 2 2 2 2 = 2
5 5 5 5 = 10
3 3 3 = 9
5 5 5 5 = 0
Решение:
2 + 2 + 2 + 2 + 2 + 2 - 2 - 2 = 8
4 + 4 + 4 - 4 - 4 = 4
2 + 2 + 2 + 2 + 2 + 2 - 2 - 2 - 2 = 6
4 + 4 + 4 - 4 - 4 - 4 = 0
5 + 5 - 5 = 5
2 + 2 + 2 + 2 + 2 - 2 - 2 - 2 - 2 = 2
5 + 5 + 5 - 5 = 10
3 + 3 + 3 = 9
5 + 5 - 5 - 5 = 0